PARASITES OF STRAY CATS IN BAGHDAD AREA - S. Kadhim, F.; K. Jassim, F.; H. Kawan , M. (The Iraqi Journal of Veterinary Medicine, 1994)
In a survey of 26 stray cats collected from different areas in Baghdad. Each cat examined for ectoparasites and gastrointestinal parasites. All cats examined were harbouring one or more species. The high rate of infection was found with Diplopylidium columbae and Physaloptera preputialis (82.6%). External parasites recorded in this study were Rhipicephalus species and Ctenocephalus felis.